2005
DOI: 10.1100/tsw.2005.52
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Buprenorphine and Methadone Maintenance Treatment: A Three-Year Follow-Up of Quality of Life Assessment

Abstract: This study was conducted to compare long-term outcome effects on the quality of life (QOL) of oral methadone with sublingual buprenorphine maintenance treatment. The QOL status of opioid-dependent patients was assessed using the German version (“Berlin Quality of Life Profile”) of the Lancashire Quality of Life Profile. Physical symptoms were measured using the Opiate Withdrawal Scale (OWS). Urine tests were carried out randomly to detect additional consumption. In the first study period, 53 opioid-dependent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
58
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 96 publications
2
58
0
4
Order By: Relevance
“…Methadone treatment is effective as both primary and secondary HIV prevention (Kerr et al 2004) and cost-effective to society (Barnett et al 2001;Doran et al 2003). In addition to improving health outcomes, methadone treatment also substantially improves the quality of life of patients over the course of methadone treatment (Giacomuzzi et al 2005). Barriers to retention in methadone treatment include the severity of drug, medical and social problems at initiation of treatment, as well as patient readiness for treatment and motivation.…”
Section: Medication Assited Treatment Utilizing Methadonementioning
confidence: 99%
“…Methadone treatment is effective as both primary and secondary HIV prevention (Kerr et al 2004) and cost-effective to society (Barnett et al 2001;Doran et al 2003). In addition to improving health outcomes, methadone treatment also substantially improves the quality of life of patients over the course of methadone treatment (Giacomuzzi et al 2005). Barriers to retention in methadone treatment include the severity of drug, medical and social problems at initiation of treatment, as well as patient readiness for treatment and motivation.…”
Section: Medication Assited Treatment Utilizing Methadonementioning
confidence: 99%
“…Methadone diminishes the euphoric effects of other opioids (cross tolerance), without necessarily causing euphoria, sedation or analgesia. This means that self-administered illicit opioids will not lead to euphoria, making it less likely that clients/patients will either use illicit opioids or overdose (Giacomuzzi, 2008). Methadone maintenance treatment has been demonstrated to be an effective treatment for opioid addiction and curbs the incidence thereof.…”
mentioning
confidence: 99%
“…Addiction is currently also defined as a form of behavior through which an individual has impaired control with harmful consequences. Thus, individuals who recognize that their behavior is harming them or those they care about find themselves unable to stop engaging in the behavior when they try to do so (Giacomuzzi, 2008). The severity of the medical, psychological and social harm that can be caused by addiction, together with the fact that it violates the individual's freedom of choice, means that it is appropriate to consider it to be a disorder of motivation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Life priorities of injection drug users include, a concern about and treatment of infectious diseases, such as hepatitis C infection, as well as, social and fiscal issues such as housing, money, and protection from violence [9]. Studies have shown that individuals receiving methadone treatment are at a reduced risk of death, less involved in crime, and have an enhanced quality of life, with positive cognitive, emotional, and social functioning [10][11][12][13].…”
mentioning
confidence: 99%